Bloody Diarrhoea anl0ng Children under five years of Age in Tikirit Teaching Hospital - Thamer Mutlek Jasim (مجله كليه طب الكندي, 2009)
ObjectiveIs to study the causes of bloody diarrhea in in (50)cases (37%) , Shigella spp in (25) cases (18% and children under five years of age and to clarify their relations Campylobacter jejuni Icases only (0.75%) to the type offood and mothers educational level ConciusionBloody diarrehea is common in children under methods Ahospital based study was carried out at tikreet 5years age who were admitted to Tikreet Teaching Hospital teaching Hospital in Tikreet city on 133 children who were in Tikreet city , There is astrong positive relationship admitted to the hospital with bloody diarrehea their ages between the occurrence of bloody diarrehea and the type of range between one month -5years. The period study is from food. Education of the mother plays an important rule for (January200 I-July 2001). the occurrence of bloody diarrehoea, mostly those who Results The pathogens causing bloody diarrhea were were illitrate